Keberlanjutan Finansial Usaha Beras Siger: Studi Kasus pada UMK peserta Model Pengembangan Pangan Pokok Lokal (MP3L) di Propinsi Lampung - Fitriani Fitriani; Sutarni Sutarni; Teguh Budi Trisnanto; Cholid Fatih; Robet Asnawi (Politeknik Negeri Lampung, 2019)
The Local Staple Food Development Model (MP3L) in Lampung Province has been developed from 2013 introducing tiwul as analog rice, known as Beras. Beras Siger program introduced analog processing technology through the use of equipment modern and improved production processes, as well as packaging. This study focuses on analyzing the financial sustainability of the Beras Siger business participants. This research is a case study. Â Beras Siger business participants in South Lampung Region in Jati Agung District selected case study. Primary data required includes ownership of land assets, buildings and equipment, production facility/input needs, production and the selling price, sales volume, revenue and income and other general descriptions. Financial analysis is performed using Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR) criteria. Based on the results of the analysis it can be concluded that the cost structure of the Beras Siger program participants showed a very high-value component of production equipment. The size of the investment value of program participants causes the business needs a minimum of 7 years to be able to obtain a profitable return. In the existing situation, the program participants' Beras Siger business will be financially feasible if they increase production capacity by 20%.